PENGARUH PERCEIVED EASE OF USE, HARGA, DAN KEAMANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION SECARA ONLINE DAN DAMPAKNYA TERHADAP KEPUASAN PELANGGAN ( Studi Kasus : Toko Online ‘’Sale Stock Indonesia‘’) - Nima, Nimayani Saputri B1021141002 (Jurnal Manajemen Update, 2017)
ABSTRACTThis reseacrh aims for test and analyze the The Effect of Perceived Ease Of Use, Price and Security on Online Fashion Product Decisions and Its Impact on Customer Satisfaction in Online Shop ‘’ Sale Stock Indonesia‘’ . This reseacrh is quantitative. Population of the research are pontianak all of  people who ever make a fashion purchase in the online store Sale Stock. The sampel of 100 respondents, sampling technique that is used in this research is purposive sampling and then the data was processed by path analysis.The results of analysis for the first model show that ease of use and price have a significant effect on purchasing decision, while the security variable has no significant positive effect on purchasing decision. Predictive capability of the three variabels on purchasing decision is 51% while the remaining 49%  was influenced by other factors not included in the research model. The results of analysis for the second model show that ease of use, price, and purchasing decision have a significant effect on customers satisfaction, while the security variable has no significant effect on customers satisfaction. Predictive capability of the  variabel on customer satisfactionis 62% while the remaining 38% was influenced by other factors not included in the research model.  Keywords: ease of use, price, security,purchasing decision , customer satisfaction